2014
DOI: 10.1109/twc.2014.2339845
|View full text |Cite
|
Sign up to set email alerts
|

Energy Cooperation in Cellular Networks with Renewable Powered Base Stations

Abstract: In this paper, we propose a model for energy cooperation between cellular base stations (BSs) with individual hybrid power supplies (including both the conventional grid and renewable energy sources), limited energy storages, and connected by resistive power lines for energy sharing. When the renewable energy profile and energy demand profile at all BSs are deterministic or known ahead of time, we show that the optimal energy cooperation policy for the BSs can be found by solving a linear program. We show the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(113 citation statements)
references
References 18 publications
0
113
0
Order By: Relevance
“…Recent studies show that such systems can offer significant energy savings if a joint energy and communication cooperation approach will be implemented. Actually, in the [18] and [19] novel paradigm based on the transfer of energy between BSSs over the electrical grid is presented, where the grid can be considered as an energy reservoir with ideally infinite capacity which enables two-way energy transfer among distributed BSSs. Such a concept allows the one BSS that has excess of energy to compensate the other that has a deficit due to either lower generation of renewable energy or higher demand of the users connected to the BS.…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies show that such systems can offer significant energy savings if a joint energy and communication cooperation approach will be implemented. Actually, in the [18] and [19] novel paradigm based on the transfer of energy between BSSs over the electrical grid is presented, where the grid can be considered as an energy reservoir with ideally infinite capacity which enables two-way energy transfer among distributed BSSs. Such a concept allows the one BSS that has excess of energy to compensate the other that has a deficit due to either lower generation of renewable energy or higher demand of the users connected to the BS.…”
Section: Related Workmentioning
confidence: 99%
“…Since the base levels are fixed within each iteration, a directional water-filling procedure [6] can be used to find the optimal power allocation. Finally, transmit powers can be calculated by finding the optimal transfer rates δ i and γ i using (14). We remark that v s,i = βv r,i for h sps,i < h rpr,i , and v s,i = v r,i /α for h sps,i ≥ h rpr,i , implying that water levels are linearly related based on which transmitter is generous in that time slot.…”
Section: Optimal Power Allocationmentioning
confidence: 99%
“…More recent developments in energy harvesting communications includes the possibility of energy transfer between nodes [3], [12], [13], [14]. Of particular relevance is reference [3] where the two-hop model with one source one relay is studied when both nodes are energy harvesting and the source can unidirectionally transfer energy to the relay.…”
Section: Introductionmentioning
confidence: 99%
“…The game is guaranteed to have at least one Nash equilibrium. Energy cooperation in energy harvesting networks has been explored recently, for instance, in [8], [9], where harvesting modules share a portion of their harvested energy with other harvesting modules. In [8], the optimal energy cooperation among a source and a relay is found that maximizes the network throughput.…”
Section: Introductionmentioning
confidence: 99%
“…The energy cooperation between two cellular BSs equipped with harvesting and hybrid modules is studied in [9]. In [9], the harvested energy and the demanded energy are considered to be deterministic and the optimal energy cooperation policy of BSs is derived.…”
Section: Introductionmentioning
confidence: 99%